PENGARUH PROMOSI, HARGA, LOKASI, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMBELIAN JASA - Ricky Aristoteles, 07.05.51.0065; Kasmari, Kasmari (Students Journal of Economic and Management, 2012)
In this research, researcher used a proportional stratified random sampling and obtain a sample size of 95 people. Data taken from the samples were then tested with the validity and reliability. The result indicates that the data are valid and have the reliability. Further analysis researcher used multiple regression to explain the relationship between variables under research. The result is the promotion, price, location, and reference groups have a positive and significant effect on purchasing decisions either partially or simultaneously. Key words: promotion, price, location, reference groups, the purchase decision